SOSIALISASI TERHADAP GEN Z TENTANG SISTEM PEMILIHAN DAN MEMAHAMI TATA CARA PROSES PEMILIHAN - Kadek Adyatna Wedananta; Dewa Ayu Diah Satyawati; Ni Nengah Rupadi Kertiriasih; Anak Agung Adi Wiryya Putra; Putu Suparna (Bajang Institute, 2025)
Generation Z (Gen Z), the younger demographic increasingly entering voting age, plays a crucial role in the democratic process. However, their understanding of the voting system and the procedures involved still needs reinforcement. This article discusses the importance of socialization among Gen Z regarding the voting system and understanding the procedures involved. Through an educational approach relevant to the current context of technology and time, socialization can enhance their participation and comprehension within the democratic process. This socialization can be carried out through various media, such as social media platforms, voter education campaigns, and formal educational programs in village. By understanding their rights and responsibilities as voters, Gen Z can become more actively involved in general elections, selecting candidates who represent their values and aspirations. Awareness of the importance of participation in the democratic process and understanding the mechanisms of voting can strengthen the foundation of an inclusive and sustainable democracy